The role of ball path curvature in basketball shooting accuracy - Slegers, N.; Love, D. (Journal of Sports Sciences, 2024)
During the shooting motion of a basketball, the path of the ball from the beginning of the lift to release follows an S-shaped trajectory. This study is the first to investigate how two distinctive features of the S-shaped ball path, the maximum curvature, Kappamax, and terminal curvature, s, are associated with longitudinal accuracy. The sagittal plane ball path and curvature were found using Bezier curves for 31 professional male basketball athletes. Terminal release curvature had a very strong positive correlation to intra-individual release velocity standard deviation (r = 0.73, p < 0.001) indicating that shooters with straighter terminal ball paths had better longitudinal shooting accuracy. It was also observed that Kappamax coincided with the transition to the forward shooting motion and that players with higher Kappamax tend to have a clear two-part shooting style rather than a single fluid motion. A comparison between groups of good and poor shooters identified a mean difference in Kappamax of 7.9 m-1 (p < 0.001, 95% CI: 11.8-4.0 m-1) suggesting that good shooters typically have a higher Kappamax than poor shooters.